Estudo sobre políticas educacionais no cenário da educação remota, em caráter excepcional em tempos de pandemia em escolas públicas municipais de João Pessoa-PB - Silva, Maria Girleny Roberto da (2024)
This research investigated the educational policies that guarantee the right to education, quality and permanence in the “Remote Education” scenario, in the pandemic context in municipal public schools in João Pessoa-PB. The COVID- 19 pandemic has brought unprecedented challenges to global education. Because of accelerated growth in the number of people infected with Covid-19, the World Health Organization (WHO) established health measures to curb its impact, which include the closure of schools and the need for social distancing, as a measure to preserve health of students, teachers and staff. At the time, remote education emerged as an immediate solution to continue providing learning opportunities to students. This research at master's level in education in the Postgraduate Program in Education (PPGE), promoted by the Federal University of Paraíba (UFPB), in the Educational Policies Research Line, has the general objective of analyzing educational policies that guarantee the right to education in terms of guaranteeing quality and permanence in times of pandemic in the “Remote Teaching” scenario. Methodologically, this is a research with an epistemethodological focus on qualitative research, of an exploratory type, including bibliographical, documentary and field research as stages – with semistructured interviews carried out. The analysis method used was based on Content Analysis, substantiated on the theoretical-practical principles of Laurence Bardin (2015). In specific terms, the research has social and scientific relevance, especially in the educational sphere, as it proposes to rethink ongoing educational policies, through discussions and theoretical-practical rescues that deal with the performance of educational policies, an important movement to deepen this debate.